Metagenome-wide association study of gut microbiome revealed novel aetiology of rheumatoid arthritis in the Japanese population. Issue 1 (7th November 2019) - Kishikawa, Toshihiro; Maeda, Yuichi; Nii, Takuro; Motooka, Daisuke; Matsumoto, Yuki; Matsushita, Masato; Matsuoka, Hidetoshi; Yoshimura, Maiko; Kawada, Shoji; Teshigawara, Satoru; Oguro, Eri; Okita, Yasutaka; et al.
Abstract : Objective: The causality and pathogenic mechanism of microbiome composition remain elusive in many diseases, including autoimmune diseases such as rheumatoid arthritis (RA). This study aimed to elucidate gut microbiome's role in RA pathology by a comprehensive metagenome-wide association study (MWAS). Methods: We conducted MWAS of the RA gut microbiome in the Japanese population ( n case =82, n control =42) by using whole-genome shotgun sequencing of high depth (average 13 Gb per sample). Our MWAS consisted of three major bioinformatic analytic pipelines (phylogenetic analysis, functional gene analysis and pathway analysis). Results: Phylogenetic case–control association tests showed high abundance of multiple species belonging to the genus Prevotella (e.g., Prevotella denticola ) in the RA case metagenome. The non-linear machine learning method efficiently deconvoluted the case–control phylogenetic discrepancy. Gene functional assessments showed that the abundance of one redox reaction-related gene (R6FCZ7) was significantly decreased in the RA metagenome compared with controls. A variety of biological pathways including those related to metabolism (e.g., fatty acid biosynthesis and glycosaminoglycan degradation) were enriched in the case–control comparison. A population-specific link between the metagenome and host genome was identified by comparing biological pathway enrichment between the RA metagenome and the RA genome-wide association study results. No apparent discrepancy in alpha or beta diversities of metagenome was found between RA cases and controls. Conclusion: Our shotgun sequencing-based MWAS highlights a novel link among the gut microbiome, host genome and pathology of RA, which contributes to our understanding of the microbiome's role in RA aetiology.